Capital letters in proper names. A few comments on the “Rules of Spelling and Punctuation” of the Council for the Polish Language - Rutkowski, Mariusz (Papers in Linguistics, 2025)
The article discusses the changes to Polish orthographic rules introduced by the Council for the Polish Language coming into force on 1 January 2026. The author focuses on changes relating to the use of capital letters in proper nouns. Each of the discussed changes is explained as regards its rationale and any additional implementation issues. In his conclusion, the author highlights the general nature of the introduced changes: their less stringent character and their greater openness and flexibility.